2009
DOI: 10.1007/s12640-009-9025-1
|View full text |Cite
|
Sign up to set email alerts
|

Histaminergic Activity in a Rodent Model of Parkinson’s Disease

Abstract: Rats lesioned shortly after birth with 6-OHDA have been proposed to be a near-ideal model of severe Parkinson's disease, because of non-lethality of the procedure, near-total destruction of nigrostriatal dopaminergic fibers, and near-total dopamine (DA) denervation of striatum. There are scarce data that in Parkinson's disease, activity of the central histaminergic system is increased. Therefore, the aim of this study was to determine histamine content in the brain and the effect of histamine receptor antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
4
14
1
Order By: Relevance
“…This stands in contrast to observed 5-HT fiber hyperinnervation in forebrain of rats lesioned as neonates with 6-OHDA (Nowak et al 2009). Histamine receptor antagonists, mainly thioperamide (H 3 antagonist), intensified locomotor activity, and oral activity induced by SKF 38393 (D 1 receptor agonist); and altered stereotypy intensity induced by apomorphine (D 1 /D 2 receptor agonist).…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…This stands in contrast to observed 5-HT fiber hyperinnervation in forebrain of rats lesioned as neonates with 6-OHDA (Nowak et al 2009). Histamine receptor antagonists, mainly thioperamide (H 3 antagonist), intensified locomotor activity, and oral activity induced by SKF 38393 (D 1 receptor agonist); and altered stereotypy intensity induced by apomorphine (D 1 /D 2 receptor agonist).…”
Section: Discussioncontrasting
confidence: 75%
“…In previous studies with the selective noradrenergic neurotoxin DSP-4 (Ross 1976) and the catecholaminergic neurotoxin 6-OHDA (Kostrzewa and Jacobowitz 1974) on the dopaminergic system in a rodent model of Parkinson's disease , we found that histamine content and histaminergic activity are altered (Nowak et al 2009). Both 5-HT and histamine appear to have a modulatory role in Parkinson's disease, as elevation of these amines in brain can attenuate motor disability (Nowak et al 2009). …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In those animals an increase of serotoninergic and histaminergic activity was observed in brain (Kostrzewa et al, 1992;Brus et al, 1994;Nowak et al, 2008Nowak et al, , 2009a. Additionally, we found that thioperamide, a central histamine H 3 receptor antagonist, diminished behavioral hyperactivity in rats lesioned with 6-OHDA as neonates (Nowak et al, 2008(Nowak et al, , 2009b. Therefore, the aim of this study was to examine the effect of perinatal destruction of the serotonin system in brain (i.e., 5,7-DHT treatment) on [ 3 H]glucose uptake in the brain of these rats, when adult, and effects of thioperamide.…”
Section: Introductionmentioning
confidence: 58%